Antioxidant activity, cytotoxic activity and metabolic profiling of juices obtained from saffron (Crocus sativus L.) floral by-products. (15th May 2016) - Tuberoso, Carlo I.G.; Rosa, Antonella; Montoro, Paola; Fenu, Maurizio Antonio; Pizza, Cosimo
Highlights: Juices obtained from cold-pressed saffron floral by-products were evaluated. A comprehensive study on the antioxidant activities was performed. The phenolic profile of the juices was determined by LC-DAD and LC–ESI-(HR)MS n . Floral by-products save the bioactive compounds up to two days after harvesting. Abstract: Juices obtained from cold-pressed saffron ( Crocus sativus L.) floral by-products were evaluated as a potential source of compounds with antioxidant and cytotoxic activities. Floral by-products were split in two batches for extraction 24 and 48 h after flower harvesting, respectively. The in vitro anti-oxidant activity of these extracts was tested using the FRAP and DPPH assays, and two biological models of lipid oxidation (activity in preventing cholesterol degradation and protection against Cu 2+ -mediated degradation of the liposomal unsaturated fatty acids). The cytotoxic activity was evaluated using the MTT assay. The results show that extracts obtained 48 h post-harvest contained higher levels of total polar phenols and had the highest antioxidant activity in all of the performed assays. The LC-DAD and LC–ESI-(HR)MS n metabolic profiles showed high levels of kaempferol derivatives and anthocyanins. This study suggests that juices from saffron floral by-products could potentially be used to develop new products for the food and health industry.